Penegakan Sanksi Pidana Sebagai Ultimum Remidium dalam Pelanggaran Lingkungan Hidup - Wulandari, Ayu (Journal Evidence Of Law, 2024)
In the context of environmental licensing, structural transformation is needed towards this paradigm of granting environmental permits. This is because of the concept past development is the concept of depleting natural resources, without think about environmental impacts, in the form of environmental damage and pollution. This makes the principle of economic optimization a major part of utilization of natural resources. However, recently, the concept of development that will be held must pay attention to environmental impacts, far to future, oriented towards future generations, it is necessary to carry out research law to study further regarding whether to immediately be subject to sanctions criminal law as an ultimum remedium in violations of environmental permits and what form or mechanism for its implementation. Hence, the title raised in this legal research is "Enforcement of criminal sanctions as Ultimum Remidum in Environmental Violations”.